Spacious joy an essay in phenomenology and literature - Chrétien, Jean-Louis, 1952- (Rowman & Littlefield International Ltd., 2019)
J.L. Chretien is a French public intellectual, philosopher and poet, widely published and revered in his home country and in academic circles worldwide. This translation makes his work available to an English-language audience for the first time and a crucial contribution to our understanding of the phenomenology of religious experience.